Screw dislocation impingement and slip transfer at fcc-bcc semicoherent interfaces. (August 2021) - Liu, Xiang-Yang; Capolungo, Laurent; Hunter, Abigail
Graphical abstract: Abstract: Understanding of dislocation-interface interactions at the atomistic level could provide useful insights into the mechanisms behind slip transfer, a key information for higher length-scale formulations. A systematic study of screw dislocation impingement on both Fe/Al and Fe/Cu interfaces with Kurdjumov-Sachs orientation relationship has been carried out using atomistic simulations. For the "strong" Fe/Al interface, there is appreciable dislocation delocalization, in which the change in dislocation content provided by Nye tensor analysis. Interestingly, the delocalization is significant enough that large simulation cells must be employed in order to avoid boundary effects. When the impinging dislocations are far away from the boundaries, the large accumulation of shear strains nearby the impinging dislocations at the interface causes dislocation nucleation/emission at these places. While for the "weak" Fe/Cu interface, the dislocation delocalization at the interface is notably long-range, extending more than 20 nm away from where the initial dislocations entered the interface.